Computational and Analytical Techniques for Long Dispersive Wave and Construction of Solitary Wave Solutions for Nonlinear Whitham-Broer-Kaup Equation - Iqbal, Mujahid; Seadway, Aly R.; Lu, Dianchen; Zhang, Zhengdi (Journal of Applied Nonlinear Dynamics, 2026)
The couple system of nonlinear partial differential equation under investigation base on extension of modified rational expansion method. In this article, with the help of symbolic computation Mathematica successfully constructed the various kinds of solitary wave solutions named anti-kink soliton, travelling wave solutions, bright soliton, kink soliton, dark soliton, kink dark solitons, kink bright solitons, anti-kink dark solitons, and anti-kink bright solitons for nonlinear Whitham-Broer-Kaup equation. The calculated results are very interested, different and novel which have not been investigated in past studies. The graphical demonstration of constructed solutions demonstrate by 3-D, 2-D, contour shape by computer software Mathematica. The investigated results will be play keen role in the study of nonlinear physical phenomena in nonlinear sciences and constructed results prove that EMRE approach is very efficient, reliable, powerful for the investigation of other nonlinear partial differential equations.